Sistem Informasi Kependudukan Gampong Pante Pisang Kecamatan Peusangan - Aflizar Aflizar; Riyadhul Fajri; Zulkifli Zulkifli (Jurnal Tika, 2022)
The creation of a web-based village data management information system aims to support and simplify the information system at Pante Pisang, Peusangan District, Bireuen Regency so that it is expected to be felt by the community and other apparatus in the Pante Pisang village. This system was developed using the PHP and MySQL programming languages ​​and is accompanied by using a database that is tailored to the needs in the process of designing this system. The things contained in this system include various information such as information on population data, family data, birth data and correspondence. For the design using a structured method that uses context diagrams, ERD, DFD as a tool to design a web-based village data processing information system